The Associations of PMF1, ICAM1, AGT, TRIM65, FBF1, and ACOX1 Variants With Leukoaraiosis in Chinese Population - Huang, Wen-Qing; Ye, Hui-Ming; Cai, Liang-Liang; Ma, Qi-Lin; Lu, Cong-Xia; Tong, Sui-Jun; Tzeng, Chi-Meng; Lin, Qing (Frontiers in Genetics, 2019)
Background: Leukoaraiosis (LA) is shown as white matter hyperintensities on T2-weighted magnetic resonance imaging brain scans. Together with candidate gene association studies (CGAS), multiple genome-wide association studies (GWAS) have reported large numbers of single nucleotide polymorphisms (SNPs) to be associated with LA in European populations. To date, no replication studies have been reported in independent Chinese samples. Methods: Here, we performed a candidate gene association study comprising 220 Chinese subjects with LA and 50 controls. Thirty-nine polymorphisms on 32 risk genes were selected from previous studies, and they were genotyped through matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Genetic association analysis was firstly performed in all subjects with LA. Then, the same analysis was conducted in the six random sampling cohorts of 50 LA patients, respectively. Data analyses on the associations of SNPs with LA risk were evaluated through Pearson’s χ2 and multivariate logistic regression tests. Results: We found that eight polymorphisms in six genes (PMF1, ICAM1, TRIM65, AGT, FBF1, and ACOX1) were significantly associated with LA in the genetic association tests. Except for those eight gene variants, 24 other polymorphisms were not found to be significantly associated with LA in general genetic model, dominant model, recessive model, or multiplicative model. Among those eight polymorphisms, rs2984613 in PMF1 showed significant association with LA in the cohort of 220 LA subjects, and such significant association remained in both general genetic model (OR: 0.262, 95% CI: 0.091–0.752, padj = 0.030) and recessive model (OR: 0.323, 95% CI: 0.119–0.881, padj = 0.038) when controlling for clinical variables. Seven other significant variants (rs5498 in ICAM1, rs699 in AGT, rs2305913 in FBF1, rs1135640 in ACOX1, and rs3760128, rs7214628, and rs7222757 in TRIM65) were identified in those six random sampling tests that were conducted in the adjusted cohorts of 50 LA patients. In addition, except for rs699 which showed detrimental effect and represented a risk variant for LA, seven other polymorphisms seemed to exert protective effects on LA and to reduce the risk of LA. It is necessary to confirm these associations in an independent cohort. Conclusions: This first replication study on multiple genes in an independent Chinese population did not replicate any risk polymorphisms for LA other than rs 699 in AGT but revealed the significantly negative associations of PMF1, ICAM1, TRIM65, FBF1, and ACOX1 polymorphisms with LA. It not only supported the strong ethnic differences in the genetics of LA but also indicated that those six identified genes may be involved in Chinese white matter lesions. Larger scales of CGAS and GWAS are necessary to confirm and decipher those ethnic-Han specific risk genes for LA in China.